WILLIAM SHAKESPEARE'S LEGACY IN 21ST CENTURY - Yuldasheva Mahinur Baxodir qizi; Khamitov Eldorbek Erkin o'g'li (Ta'lim innovatsiyasi va integratsiyasi, 2024)
Abstract: William Shakespeare, often considered the greatest playwright in English literature, continues to have a significant impact on culture and society in the 21st century. This article explores the enduring legacy of Shakespeare's works, analyzing how his plays, characters, and themes are still relevant and influential in contemporary times. Through a review of scholarly articles, analyses, and adaptations, this article highlights the continued importance of Shakespeare's work in shaping literature, theater, and the arts in the modern era.